2008
DOI: 10.1038/nmeth.1278
|View full text |Cite
|
Sign up to set email alerts
|

Infrared laser–mediated gene induction in targeted single cells in vivo

Abstract: We developed infrared laser-evoked gene operator (IR-LEGO), a microscope system optimized for heating cells without photochemical damage. Infrared irradiation causes reproducible temperature shifts of the in vitro microenvironment in a power-dependent manner. When applied to living Caenorhabditis elegans, IR-LEGO induced heat shock-mediated expression of transgenes in targeted single cells in a more efficient and less deleterious manner than a 440-nm dye laser and elicited physiologically relevant phenotypic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
214
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(217 citation statements)
references
References 15 publications
3
214
0
Order By: Relevance
“…The IR laser-evoked gene operator (IR-LEGO) system is a new microscopic method optimized to heat cells by using an IR laser. We confirmed that this system was efficient in regulating spatiotemporal gene expression, and reported IR laser-mediated gene induction in single targeted cells in nematodes (Caenorhabditis elegans), 9 and the local gene expression in various tissues, such as the muscle, notochord, and retina in some living vertebrates, for example, zebrafish (Danio rerio) and medaka (Oryzias latipes). 10 In this study, we applied this IR-LEGO system to the vascular system in zebrafish and established, to the best of our knowledge, for the first time, an excellent method to induce laser-mediated gene expression in single targeted endothelial cells in vivo.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…The IR laser-evoked gene operator (IR-LEGO) system is a new microscopic method optimized to heat cells by using an IR laser. We confirmed that this system was efficient in regulating spatiotemporal gene expression, and reported IR laser-mediated gene induction in single targeted cells in nematodes (Caenorhabditis elegans), 9 and the local gene expression in various tissues, such as the muscle, notochord, and retina in some living vertebrates, for example, zebrafish (Danio rerio) and medaka (Oryzias latipes). 10 In this study, we applied this IR-LEGO system to the vascular system in zebrafish and established, to the best of our knowledge, for the first time, an excellent method to induce laser-mediated gene expression in single targeted endothelial cells in vivo.…”
supporting
confidence: 63%
“…These movements seemed to influence the leakage of heat stress and made it difficult to diminish gene induction in nontargeted cells. Furthermore, applying the irradiating IR laser to the tissue resulted in intense heating of the elliptic region elongated vertically just before the focus, 9 suggesting that the muscle cells located in the vertical region of the optical axis were easily influenced by the laser. We attempted some modification of the IR-LEGO system by interrupting the center of the irradiated laser before focusing and tried to reduce the leakage to the surrounding cells in the vertical region.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, optical regulation of gene expression (1)(2)(3)(4)(5)(6)(7)(8) and optogenetic control of receptor and channel proteins on the cell surface (9-13) have received much research attention. Heat shock proteins (HSPs) are critical components of a cell's defense mechanism against injury associated with adverse stresses (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Heat shock proteins (HSPs) are critical components of a cell's defense mechanism against injury associated with adverse stresses (14)(15)(16)(17)(18). Promoters that contain heat shock elements (HSEs) upstream of the HSP coding region, known as heat shock promoters, can be turned on by various stresses besides heat shock, including heavy ions, radicals, alcohol, and viral infection, suggesting that they are driven by almost all kinds of stresses (1)(2)(3)(4)(5)(6)(7)(8)(14)(15)(16)(17)(18). Given the simple and highly controllable nature of heat shock treatment, the heat shock response is ubiquitous in all organisms from bacteria to higher vertebrates.…”
mentioning
confidence: 99%
“…On one hand, the NIR laser heating, by water absorption to photons, actually stimulated the whole cells. For example, Y. Kamei et al showed quantitative analysis on thermal distribution by a NIR laser at 1480 nm in C. elegans and photothermal effect induced gene expression [75]. On the other hand, TRP channels were nonselective cation channels through which other cations could also enter cells.…”
Section: Cell Calcium Modulation By Optogenetics and Thermogeneticsmentioning
confidence: 99%